Activities and participation of children with cerebral palsy: parent perspectives. (6th November 2015) - Mei, Cristina; Reilly, Sheena; Reddihough, Dinah; Mensah, Fiona; Green, Julie; Pennington, Lindsay; Morgan, Angela T.
Abstract: Purpose : To explore parents' views of the activities and participation of children with cerebral palsy (CP) with a range of communicative abilities and the factors (personal and environmental) that influenced these. Methods : Thirteen parents of children with CP aged 4—9 years participated in semi—structured individual interviews. Interviews were recorded, transcribed and analysed thematically. Identified codes and themes were mapped to the domains of the International Classification of Functioning, Disability and Health — Children and Youth Version (ICF-CY). Results : Parents' responses reflected all ICF-CY domains comprising activity, participation and environmental factors. Codes were primarily mapped to the domains learning and applying knowledge, communication, mobility and interpersonal interactions and relationships . Key barriers identified included aspects of parents' own interactions with their child (e.g. not offering choices), unfamiliar people and settings, negative attitudes of others and children's frustration. Facilitators included support received from the child's family and school, being amongst children, having a familiar routine and the child's positive disposition. Conclusions : Despite the barriers experienced, children participated in a range of activities. Parents placed importance on communication and its influence on children's independence, behaviour and relationships. Barriers and facilitators identified highlight aspects of the environment that could be modified through intervention to enhance communication and participation. Implications for Rehabilitation: Children's activities and participation were largely related to early learning tasks (e.g. literacy), communication, mobility and interactions. Intervention aimed at improving activities and participation may address the various child, impairment, social and environment factors identified here as impacting on activities and participation (e.g. the child's personal characteristics, communication and physical impairments, the support and attitudes of others and the familiarity of the environment). Therapists will need to consider (and manage) the potential negative impact communication deficits may have on children's behaviour, independence and social skills which may in turn detrimentally impact on activity and participation.